Implementasi Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Kemampuan Berkomunikasi Siswa Mata Pelajaran Pendidikan Pancasila Kelas IV di SD Negeri 121/I Muara Singoan - Ariyani, Vera; Sofwan, Muhammad; Khoirunnisa, Khoirunnisa (Universitas Batanghari Jambi, 2025)
This study aims to improve students' communication skills by using the Two Stay Two Stray cooperative learning model in grade IV of SD Negeri 121/I Muara Singoan. The research data was obtained by conducting classroom action research (CAR) consisting of two cycles, where the data taken were in the form of research data through observation, interviews and documentation. The data in this study were analyzed quantitatively and qualitatively. The results of this study prove that the use of the Two Stay Two Stray cooperative learning model can improve students' communication skills in grade IV of SD Negeri 121/I Muara Singoan.